Komisi Pemberantasan Korupsi Sebagai Lembaga Negara UUD 1945: Sebuah Analisis - Ulum, Muhammad Bahrul; Al Farizi, Dizar; Dewanti, Ria Resti (Lentera Hukum, 2015)
Currently, the Corruption Eradication Commission (KPK) is regulated by law, which is considered to have an inferior institutional status and affect the performance of corruption eradication in Indonesia. This institutional inferiority can be judged on the basis of authority and institutions. This paper specifically discusses the institutional status of the Corruption Eradication Commission which is considered inferior and builds discourse through efforts to include the Corruption Eradication Commission as a state institution regulated in the 1945 Constitution. The analysis of this institution as a non-state institution that is not directly outlined in the 1945 Constitution influences its power in efforts to eradicate corruption. Keywords: Corruption Eradication Commission, State Institution, State Commission.